(3BaGb LOjOI aj JYdje GdcHGQ (B/s - (3LGeYI Yjf TeS(B.s (3eQcR JYdje GdcHGQs ((3GdbGgQI (B:s (3LGeYI Yjf GdTeS, eQcR JYdje GdcHGQs)
(3aj eMh GdCejI hJYdje GdcHGQ(B.s
(3BNQ YOO Je GdQLhY Edjg(B: (3Y(B11 ((3jfGjQ (B2012(3e(B- 1433(3g`(B)s
(3WQjbI GdhUhd (B: (3THcI GdEfJQfJ(B.s
(3BNQ YOO Je JOGhdg (B: (3Y(B. 28 ((3jhfjh (B2020)s
(3JGQjN GdGWdGY (B: 31 / 12 / 2020.s
(3GdhUa eCNhP ef (B: (3Y(B. 7 ((3jhfjh (B2008)s
Keywords: (3eMh GdCejIs -- (3OhQjGJs; (3JYdje GdcHGQs -- (3OhQjGJs